PENERAPAN POLA PEMBIMBINGAN DEMOKRATS DALAM MENGEMBANGKAN SIKAP KEDISIPLINAN PADA ANAK USIA DINI DI PAUD BAITUL ILMI KABUPATEN BEKASI - Dwi Santika Saptia Juniar; Nia Hoerniasih; Pujiarto (Comm-Edu (Community Education Journal), 2026)
This research is motivated by the low level of discipline among students at PAUD Baitul Ilmi in Bekasi Regency. This study aims to determine the application of democratic guidance patterns in developing discipline attitudes in early childhood at PAUD Baitul Ilmi in Bekasi Regency. This study uses a qualitative descriptive research approach. Data collection methods used are observation, interviews, and documentation. The results show that the application of democratic guidance patterns on the development of children's discipline has a positive impact on children's behavior, which is characterized by an increased ability to obey rules, take responsibility for shared activities and facilities, and the courage to express opinions and control behavior.